Analisis Kemampuan Koordinasi Tendangan Sabit dan Pukulan Depan Atlet Pencak Silat PSN Perisai Putih Ranting Batang-Batang - Ach Noval Akbar; Winda Nuraisyah; Rendra Kusuma (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the coordination ability of crescent kicks and front punches among 15 athletes at PSN Perisai Putih Ranting Batang-Batang (12 males, 3 females). Employing a descriptive quantitative approach with a survey technique, data were collected through a 30-second coordination test performed three times. Descriptive statistical analysis revealed that the athletes' coordination ability is generally in the Good category at 53%. Specifically, 20% of athletes reached the Very Good category, 27% were in the Sufficient category, and no athletes fell into the Poor or Very Poor categories. Interestingly, all female athletes reached the good to very good standards, while male athletes showed more variation due to different assessment norms. It is concluded that the current training program is sufficiently effective, though more structured, varied, and intensive programs are needed, especially for those in the sufficient category, to optimize movement synergy and strike accuracy in competition.